A (Very Slightly Critical) Encomium to the SOEP - Daniel S. Hamermesh (Vierteljahrshefte zur Wirtschaftsforschung, 2008)
The SOEP is the second most widely-used household survey worldwide (behind the American PSID), and it is used far beyond the German-speaking world. Partly this widespread usage is due to the helpful translations of the codebooks and variable names and the homogenization of the dataset by the Cornell group in the CNEF. Partly too, it has resulted from the data themselves - their breadth and the care with which they have been collected. The biggest strength of the SOEP is, of course, the remarkably high quality of the data. Few researchers appreciate this - we use whatever data we can lay our hands on to develop/ test our theories. We economists are among the worst sinners in this dimension. The SOEP's biggest strength has been its continuing renewal - adding refresher and additional samples that concentrate on new populations of interest. The expansion to include the Neue Länder in 1990; the enlargement of the immigrant sample; and particularly the inclusion of special samples, such as that of high-income households, have both maintained the representativeness of the survey and, more important in my view, created the SOEP's unique status as a source of longitudinal information on particular sub-populations. The renewals of the sample are the biggest assurance to researchers and to the policy and intellectual publics that, we hope, pay attention to our work, that any results reflect contemporary experience in Germany..
Keywords: 330; Panelforschung; Privater Haushalt; Deutschland